If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 26 = 8x + 12 Reorder the terms: 26 + 6x = 8x + 12 Reorder the terms: 26 + 6x = 12 + 8x Solving 26 + 6x = 12 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 26 + 6x + -8x = 12 + 8x + -8x Combine like terms: 6x + -8x = -2x 26 + -2x = 12 + 8x + -8x Combine like terms: 8x + -8x = 0 26 + -2x = 12 + 0 26 + -2x = 12 Add '-26' to each side of the equation. 26 + -26 + -2x = 12 + -26 Combine like terms: 26 + -26 = 0 0 + -2x = 12 + -26 -2x = 12 + -26 Combine like terms: 12 + -26 = -14 -2x = -14 Divide each side by '-2'. x = 7 Simplifying x = 7
| 3y+-1=7 | | (3x-10)=(3x-2) | | 3x^2+y^2=4 | | M^2+8+16=0 | | 3y+2ln(x)=4ln(y+7) | | (-3+106)=(7x-64) | | (5x+49)=(3x+57) | | 8sin^2x-7=-2cosx | | 10x+4y=52 | | 10x-4y=52 | | F(9)=4(9)-2 | | 3sint-sint=0 | | cos^10x-sin^10x=1 | | 3x+5x=6x | | sqrt(x+15)+15=-sqrt(x) | | 192/4=x/1 | | 1.79266204420746E-308=0 | | X=-4t+2t^2 | | 75=5x^2-20x | | z+y=1 | | (x+17)(x-22)=0 | | 6(-2-5x)=168 | | 3k+3=k+4 | | 3.1e+4= | | 2/a/1/a•a | | 5x-14-4x+5=90 | | 2/a/1/axa | | y=10+8(x-10) | | 7x-2-3x+12=90 | | y=3x^2+12+9 | | 2/a/1/a2 | | 5x-10-4x+28=180 |